2006
DOI: 10.1038/sj.jp.7211437
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical cord nucleated red blood cell counts: normal values and the effect of labor

Abstract: Objective: To determine the umbilical cord blood nucleated red blood cell (UC-nRBC) count in uncomplicated pregnancies delivered by elective cesarean section or delivered vaginally.Methods: A total of 57-term singleton pregnancies were studied: 33 with elective cesarean sections and 24 with vaginal deliveries. UC-nRBC was analyzed for its nucleated red blood cell counts. A logarithmic transformation of the data was used for statistical analysis.Results: The mean±standard deviation (s.d.) for nucleated red bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 23 publications
3
28
0
Order By: Relevance
“…Our results only correlate with the results of Boskabadi et al [7] who carried out a study on 48 perinatally asphyxiated neonates and the most common mode of delivery was normal vaginal route in 34 of these babies. In a study by McCarthy et al [8] concluded that stress of uncomplicated labor does not change NRBC levels. Thus the variation in different studies regarding the mode of delivery may be explained by the fact that neonatal encephalopathy may originate early in neonatal period in some cases of HIE.…”
Section: Discussionmentioning
confidence: 99%
“…Our results only correlate with the results of Boskabadi et al [7] who carried out a study on 48 perinatally asphyxiated neonates and the most common mode of delivery was normal vaginal route in 34 of these babies. In a study by McCarthy et al [8] concluded that stress of uncomplicated labor does not change NRBC levels. Thus the variation in different studies regarding the mode of delivery may be explained by the fact that neonatal encephalopathy may originate early in neonatal period in some cases of HIE.…”
Section: Discussionmentioning
confidence: 99%
“…20 The increased erythropoiesis is probably due to both an increase in erythropoietin levels and a direct hemopoietic effect of hyperinsulinaemia. [21][22][23] The importance of estimation of alkali resistant hemoglobin cannot be over emphasized in a resource poor country like India which also has the dubious distinction of having a prevalence of thalassemia. 24,25 While majority of the hemoglobin in the fetus is alkali resistant, the proportion rapidly decreases in the first year of life.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been suggested that increased NRBC count is not only the marker of perinatal asphyxia, but also predicts the risk of consequences of neurological development. 15,21,33,34 Although the exact mechanism is unclear, it may be relevant to increase the umbilical cord blood erythropoietin levels in 1 to 4 hours after acute asphyxia. Increased secretion of erythropoietin results in increased release of NRBCs from the bone marrow due to increased mitotic divisions of normoblasts.…”
Section: Discussionmentioning
confidence: 99%